Benchmarking microbiome transformations favors experimental quantitative approaches to address compositionality and sampling depth biases - Verónica Lloréns-Rico (Nature Portfolio, 2021)
Here, the authors use simulated quantitative gut microbial communities to benchmark the performance of 13 common data transformations in determining diversity as well as microbe-microbe and microbe-metadata associations, finding that quantitative approaches incorporating microbial load variation outperform computational strategies in downstream analyses, urging for a widespread adoption of quantitative approaches, or recommending specific computational transformations whenever determination of microbial load of samples is not feasible.